The Influence of Liquidity, Solvency, and Exchange Rate to Company Profitability and It’s Implication to Stock Price at Mining Sector Company - Hari Gursida (STKIP Singkawang, 2017)
This study aims to determine the effect of Liquidity, Solvency, and Exchange Rates on Stock Price, either directly or indirectly through Profitability. This research uses descriptive quantitative approach by using mining sector company listed in BEI period 2011-2015 as its object. Sampling method used is purposive sampling, so there are 11 companies that meet the criteria as a sample. This research proxy liquidity variable with cash ratio, solvency with debt to asset ratio, exchange rate with rupiah exchange rate to USD, profitability with return on asset. The estimation method used in this research is Structual Equation Modeling to test the research hypothesis. Based on the results of research indicate that Cash Ratio, DAR, and Exchange Rate does not directly influence Stock Price, while ROA has direct effect on Stock Price. Cash Ratio, DAR, and Exchange Rate have a significant effect on Stock Price through ROA as moderating variable.